HVDC Transmission Line Protection Based on Transient Power. (2016) - Tom, Sherin; Thomas, Jaimol
Abstract: This paper presents a new protection method for High Voltage Direct Current (HVDC) system based on transient power. Behavior of the HVDC system during fault is studied. Variation of transient power and the relation between various parameters of the line are analyzed during each fault. Based on that the protection principle is developed. Transient power is obtained by measuring the voltage and current at the two terminals of the line. Identification of internal and external faults as well as location of DC lone fault can be done correctly and quickly from transient power. The test system is modeled using MATLAB - SIMULINK based on first CIGRE HVDC benchmark system.